(3SdWGJ eCehQ GdVQGFH aj GdLQGFe GdVQjHjI (B/ s - (3CMeO YHOGdUHhQ Jhajb HNjJs; (3WGQb CMeO aJMj SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3MjK Gf ehVhY SdWGJ eCehQ GdVQGFH aj GdLQGFe GdVQjHjI Je JfGhdg ef NdGd fU GdeGOI (B23 (3ef bGfhf GdGLQGAGJ GdLfGFj(B. (3hGdhGbY Gf SdWGJ eCehQj GdVQGFH GdeNhdI dge aj eQMdI LeY GdGSJOdGdGJ hgi Gfg jbhe HaMU GdHdGZGJ hGdTcGhj hGdGWdGY hGdeYGjfI hGNP GdYjfGJ hGdGSJjaGA hYed eMGVQ VHW hefGbTI haMU ddOaGJQ hGdeSJfOGJ hGdSLdGJ GdeJYdbI HGNJUGUg hYedg hGjVG jbhe eCehQ GdVQGFH aj eQMdI GLQGAGJ GdJMbjb GSJKfGAG HGdbHV hGdJaJjT hGdfOH ddLGf hGf gPg GdSdWGJ GdeNhdI dg eSJeOg ef UaI GdVHWjI GdbVGFjI GdNGUI WHbG dfU GdeGOI (B23 (3ef bGfhf GdGLQGAGJ abQg bHd GdGNjQIh GdbhGfHf GdVQjHjI GdNGUI hHPdc jNVY eCehQ GdVQGFH aj TGf gOg GdSdWGJ GdeNhdI dg YfO GdbjGe HCYeGdge ddbhGfjf GdVQjHjI GdNGUI h dbGfhf GdGLQGAGJ GdLfGFjI GdPj jMOO hjfXe GNJUGUGJ eCehQ GdVHW GdbVGFj HUaI YGeI s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2015(3, bSe GdbGfhf GdLfGFjs
(3HHdjhLQGajG(B: (3UaMGJ (B183-195s
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQGFe GdVQjHjIs; (3GdSdWGJs; (3eCehQ GdVQGFHs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs